2016
DOI: 10.1089/neu.2015.4349
|View full text |Cite
|
Sign up to set email alerts
|

Depression Trajectories during the First Year after Traumatic Brain Injury

Abstract: Major depression is prevalent after traumatic brain injury (TBI) and associated with poor outcomes. Little is known about the course of depression after TBI. Participants were 559 consecutively admitted patients with mild to severe TBI recruited from inpatient units at Harborview Medical Center, a Level I trauma center in Seattle, WA. Participants were assessed with the Patient Health Questionnaire-9 (PHQ-9) depression measure at months 1-6, 8, 10, and 12 post-injury. We used linear latent class growth mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 73 publications
6
39
0
2
Order By: Relevance
“…Furthermore, being unemployed or impoverished at the time of injury or substance abuse before or at the time of injury also conferred a higher likelihood of developing PTD 8,12,13,15,94. Personality characteristics and pre-injury psychiatric conditions that increase the risk of sustaining a TBI95,96 may also put individuals at greater risk for developing PTD 7,85,94. In fact, one of the biggest predictors of PTD was a pre-injury history of depression or other psychiatric disorder 7,94,97.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, being unemployed or impoverished at the time of injury or substance abuse before or at the time of injury also conferred a higher likelihood of developing PTD 8,12,13,15,94. Personality characteristics and pre-injury psychiatric conditions that increase the risk of sustaining a TBI95,96 may also put individuals at greater risk for developing PTD 7,85,94. In fact, one of the biggest predictors of PTD was a pre-injury history of depression or other psychiatric disorder 7,94,97.…”
Section: Discussionmentioning
confidence: 99%
“…30 All of these measures have established reliability and validity for use with persons with TBI. 18,21,23,24,[31][32][33][34][35][36] The PHQ-9 was analyzed as a dichotomous variable: likely major depression vs. no major depression. 36 When the person with TBI was not able to complete the follow-up, the SWLS and PHQ-9 were not administered and the FIM and PART-O-17 were based on a proxy report.…”
Section: Secondary Outcomes Included: Functional Independence As Measmentioning
confidence: 99%
“…There is substantial heterogeneity associated with TBI and while not all patients with TBI develop depression, studies have shown that some survivors become depressed early, others become depressed in the post-acute stage and others have sub-threshold depressive symptoms that can lead to later depression. 21 Contributory factors to the onset and course of post-TBI depression include the extent of social support and post-acute services, preinjury mental health disorders, injury related changes and posttraumatic adaptive issues. Gender, age and level of education are important in some studies but not in others.…”
Section: Introductionmentioning
confidence: 99%
“…2 Once depression becomes established it likely becomes more difficult to treat and many individuals post-TBI require medications over extended periods for depression. 21,22 Given the high prevalence of depression post-TBI, consideration of a preventative approach may be an option and indeed a desirable goal for clinicians, patients and carers. Secondary prevention aims to reduce the impact of a disease or injury that has already occurred.…”
Section: Introductionmentioning
confidence: 99%